Morphological and Behavioral Correlates of Long-Term Bird Survival in Selectively Logged Forest - Srinivasan, Umesh (Frontiers in Ecology and Evolution, 2019)
The response of biodiversity to land-use change has been a central focus in applied ecological research for close to half a century. However, despite a vast body of literature, our understanding of how species traits influence demographic vital rates in anthropogenically-modified habitats is remarkably scant. Such an understanding is crucial because vital rates determine population viability in modified habitats, and underlie emergent occupancy, abundance and community-level patterns. I use 5,298 captures of 3,310 individuals of 20 species across seven years to test how four traits—(a) inherent survival, (b) body size, (c) social behaviour, and (d) migratory strategy—influence annual survival in selectively logged versus intact forest in tropical montane eastern Himalayan birds. In general, variation in body mass and alternative behavioural strategies (e.g., mixed-species flocking versus solitary behaviour) were not associated with survival differences in intact forest. However, species with high inherent survival, year-round residents, and species that did not participate in mixed-species flocks had appreciably lower survival in logged forest compared with intact forest. Solitary foragers, for instance, faced a 30% decline in survival in logged forest compared with intact forest. Non-migratory habit and solitary foraging behaviour might make species vulnerable to extinction in logged forest through reduced survival, an especially important process in influencing population viability. Identifying how species’ traits modulate their response to land-use change by altering survival rates is crucial to predict species responses to forest modification, and to better plan and manage biodiversity-friendly forest use.